A wide perspective of carbon materials as catalysts for bioremediation of emerging pollutants and methanogenesis - Pereira, Luciana (2019)
Biotransformation of emerging pollutants under anoxic conditions can be accelerated by carbon materials (CM) acting as redox mediators. CM have been also extensively reported as facilitating external electron transfer in methanogenic processes. Here, different CM including magnetic carbon materials (C@MNP), were prepared, characterized and applied as RM on the biological reduction of Acid Orange 10 (AO10) and ciprofloxacin (CIP). CIP could be biologically removed in the presence of CNT and CNT@2%Fe, and AO10 decolourisation rates were 79-fold higher in the assays with CNT@2%Fe. The effect of carbon nanotubes (CNT) on the activity of several pure cultures of methanogens was also investigated, demonstrating that CNT could accelerate up to 17-fold the methane production rate. It is evident from this work that carbon materials with different chemical and textural characteristics can accelerate significantly bioremediation and methanogenic processes. The fact that concentrations as low as 0.1 g/L were used with positive effects, is remarkable in terms of economic feasibility of using CM as efficient catalysts in both processes.